Komandinio darbo ir asmeninės lyderystės raiška slaugytojo darbe - Mikalauskienė, Agnė; Rapolienė, Lolita; Truš, Marija (Slauga. Mokslas ir praktika, 2025)
Teamwork and personal leadership are key factors that help ensure a suitable working environment, quality services and work efficiency. The purpose of the study was to analyze the teamwork and personal leadership and their correlation in nursing. Research methodology. The quantitative study was conducted in one of Klaipėda City healthcare institutions in 2024. 189 nurses working in teams participated in the research. TeamSTEPPS and Leadership Practices Inventory questionnaires were used, and SPSS for Windows version 21.0 was used for statistical analysis. Research results. The vast majority of nurses, regardless of their working experience, rated teamwork as good, whereas one fifth of them perceived it as moderate. The nurses issued the highest scores to such aspects as the monitoring of the situation, the team structure and communication, whereas the lowest grades were given to the provision of mutual support. The situation monitoring and team structure factors were reliably rated higher by nurses having less working experience. The majority of nurses, regardless of their work experience, positively assessed leadership, half of them believed to have sufficient leadership qualities, one third of the nurses were using the transformational leadership style in their work, and more than one third did not consider themselves to be leaders. The nurses named responsibility, professionalism, and communication as the most important features of a leader. The most prominently expressed factors of personal leadership among the nurses were encouraging others and setting an example, while the least expressed aspect was persuasion by vision. It was established that, as the respondents’ working experience increases, the leadership factor of their challenge to the process decreases significantly. The study found a direct correlation between the personal attitudes of most nurses on teamwork and their expression of leadership. Leading by example, persuading on the vision, and empowering others reliably improved all factors of team attitudes. Conclusions. The most important team attitudes are the monitoring of situation, and team structure and communication, while the most prominently expressed personal leadership factors are the encouragement of others and setting an example. The reliable direct connection between most of the team and leadership factors show that, by strengthening personal leadership, it is possible to exert a positive influence on teamwork, which would improve work results, and, by strengthening the team structure, situation monitoring and communication, all leadership features can be developed.